2022
DOI: 10.1017/s0954394522000151
|View full text |Cite
|
Sign up to set email alerts
|

Medium-shifting and intraspeaker variation in conversational interviews

Abstract: We investigate the impact of medium of communication (in-person versus video) on intraspeaker variation in conversation—a process we refer to as medium-shifting. To quantify the effects of medium-shifting and understand its possible motivations, we analyze three variables that show intraspeaker effects of “clear” or “careful” speech: articulation rate, density-controlled vowel space area, and (ING). The data come from matched in-person and video-mediated interviews with thirty-three repeat guests from The Late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…Linguists have become interested in the effects of interacting with devices on people's language use. For instance, during the COVID-19 pandemic, a number of studies found that users were making adjustments to their speech as a result of having their conversations with other people mediated by devices or software such as Zoom or Facetime (e.g., Bleaman et al, 2022).…”
Section: User Experience and Device Impacts On User Languagementioning
confidence: 99%
“…Linguists have become interested in the effects of interacting with devices on people's language use. For instance, during the COVID-19 pandemic, a number of studies found that users were making adjustments to their speech as a result of having their conversations with other people mediated by devices or software such as Zoom or Facetime (e.g., Bleaman et al, 2022).…”
Section: User Experience and Device Impacts On User Languagementioning
confidence: 99%